Strategy For Improving The Development Of Ppatk Employees' Competence In The Administrative And Leadership Division - Pangaribuan, Delvi Adri Rahmadana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to determine how the implementation of employee competency development is carried out in the Financial Transaction Reports and Analysis Center (PPATK) in the Leadership Administration Section. Second, to identify factors that influence the improvement of employee competency development in the Financial Transaction Reports and Analysis Center (PPATK) in the Leadership Administration Section. Third, to determine the right strategy in an effort to improve employee competency development in the Financial Transaction Reports and Analysis Center (PPATK) in the Leadership Administration Section. This study focuses on an in-depth analysis of existing problems with the aim of finding comprehensive solutions. The qualitative method used allows researchers to explore various perspectives and data in depth. Based on this study, it is concluded that competency development at PPATK, especially in the Leadership Administration Section, has been carried out through classical and non-classical training. However, only around 60% of the 2024 target has been achieved, with obstacles such as limited training opportunities, budget, and relevant materials. Other inhibiting factors include low employee motivation to improve competence and organizational policies that limit resource allocation. To overcome this problem, solutions that can be implemented include collaboration with internal training provider units, development of training needs databases, utilization of non-classical methods, and socialization to increase employee motivation